Coaching, mentoring, and managing : a coach guidebook - Holliday, Micki (Career Press, 2001)
Inspire Employees-Don't "Boss" Them This book offers hundreds of practical, easy-to-learn techniques every manager can use to coach employees to become more productive, positive, inspired and effective. Filled with real-world advice and management-changing exercises, this manual shows how to get the most from employees in today's era of downsizing, layoffs, buyouts and mergers. Managers will develop the attitude, the skills, and the strategies to become more like a coach and less like a boss. They will also learn: • How to instill team vision • Five insights of high performance coaches • Ten tools for building a solid team foundation • Eight hurdles to performing the coaching role • A checklist for responding to team troubles • Five ways to quiet complaints • And much, much more! This invaluable management resource will also show managers how a mentoring attitude will help tap into the hidden strengths and talents of employees. They will see how they can inspire peak performers to even greater levels of productivity and learn effective ways to confront inappropriate behavior. Coaching, Mentoring and Managing will supply the tools to make good employees, exemplary and turn problem employees into productive workers. All in all, Micki Holliday reveals the secrets of coaching that will enable the reader to be a winner and to teach others how to be winners. She presents the skills to empower those, responsible for working with people, to become good coaches-to be able to lead and inspire their employees to work as a team and produce winning results.